Nature of Science: Effect of Professional and Sociodemographic Variables [Naturaleza de la Ciencia: Efecto de Variables Profesionales y Soc Iodemográficas] - Tecpan-Flores, S (Pontificia Universidad Javeriana, 2017)
A quantitative relational study is presented in this article. This study was conducted with high school teachers in Mexico, who studied a diploma in scientific competence, in order to diagnose the conceptions of the nature of science and its relationship with sociodemographic variables and professional status. We used an electronic version of the Science, Technology and Society Opinions Questionnaire (Manassero, Vázquez & Acevedo, 2001). Results agree with previous research studies: teachers conceptions of nature of science are mainly "naive" (Garritz, Rueda & Robles, 2011). Sociodemographic variables showed a greater influence in the conceptions of the nature of science than in those regarding professional status. Limitations of the study are discussed.